Enhancing Stability of Camelid and Shark Single Domain Antibodies: An Overview - Goldman, Ellen R.; Liu, Jinny L.; Zabetakis, Dan; Anderson, George P. (Frontiers in Immunology, 2017)
Single domain antibodies (sdAbs) are gaining a reputation as superior recognition elements as they combine the advantages of the specificity and affinity found in conventional antibodies with high stability and solubility. Melting temperatures (Tms) of sdAbs cover a wide range from below 50 to over 80 °C. Many sdAbs have been engineered to increase their Tm, making them stable until exposed to extreme temperatures. SdAbs derived from the variable heavy chains of camelid and shark heavy chain-only antibodies are termed VHH and VNAR respectively and generally exhibit some ability to refold and bind antigen after heat denaturation. This ability to refold varies from 0 to 100%, and is a property dependent on both intrinsic factors of the sdAb, as well as extrinsic conditions such as the sample buffer ionic strength, pH, and sdAb concentration. SdAbs have also been engineered to increase their solubility and refolding ability, which enables them to function even after exposure to temperatures that exceed their melting point. In addition, efforts to improve their stability at extreme pH and in the presence of chemical denaturants or proteases have been undertaken. Multiple routes have been employed to engineer sdAbs with these enhanced stabilities. The methods utilized to achieve these goals include grafting complementarity-determining regions (CDRs) onto stable frameworks, introduction of non-canonical disulfide bonds, random mutagenesis combined with stringent selection, point mutations such as inclusion of negative charges, and genetic fusions. Increases of up to 20 °C have been realized, pushing the Tm of some sdAbs to over 90 °C. Herein, we present an overview of the work done to stabilize sdAbs derived from camelids and sharks. Utilizing these various strategies sdAbs have been stabilized without significantly compromising their affinity, thereby providing superior reagents for detection, diagnostic and therapeutic applications.